2007
DOI: 10.3141/2012-15
|View full text |Cite
|
Sign up to set email alerts
|

Simulation Analysis of Truck-Restricted and High-Occupancy Vehicle Lanes

Abstract: Numerous studies have reported the efficacy of high-occupancy vehicle (HOV) lane restriction and truck lane restriction implemented independently, but the simultaneous use of both restrictions on an urban freeway corridor raises numerous operational and safety issues. This research study analyzed the operational and safety experience of an 83-mi corridor of I-95 in South Florida that has both HOV and truck lane restriction. Results of a field-validated VisSim simulation model showed that high-occupancy vehicle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…A comparison between the data at these transition locations and the nonweaving sections did not reveal any significant difference. Simulation analysis studies have reported increased vehicle queue lengths around ingress and egress sections (13), and other studies have sought to develop methodologies for determining capacity reduction in HOV lanes near ingress and egress (weaving) sections (14). However, the data available in the current study do not have the granularity to allow for an exact determination of the capacity drops at the weaving sections.…”
Section: Impact Of Weavingmentioning
confidence: 89%
“…A comparison between the data at these transition locations and the nonweaving sections did not reveal any significant difference. Simulation analysis studies have reported increased vehicle queue lengths around ingress and egress sections (13), and other studies have sought to develop methodologies for determining capacity reduction in HOV lanes near ingress and egress (weaving) sections (14). However, the data available in the current study do not have the granularity to allow for an exact determination of the capacity drops at the weaving sections.…”
Section: Impact Of Weavingmentioning
confidence: 89%
“…These results imply that in order to significantly improve traffic congestion it might be more reasonable to implement a directional time of day truck restriction strategy as proposed in the current study. Siuhi and Mussa (2007) found that during peak hours, HOV lanes and car lanes experienced better travel times than did the lanes that permitted truck traffic. The leftmost lanes (including HOV lanes, which were restricted from trucks) had higher speeds than unrestricted lanes.…”
Section: Flow Speed Travel Time and Traffic Operations Studiesmentioning
confidence: 95%
“…Garber and Liu, 2007) accident rates per vehicle-mile increase with volume, but costs fall because of reduced accident severity. Lane changes per vehicle-mile -which are correlated with accident rates -increase with the fraction of trucks in the traffic volume up to about 25%, but drop beyond that (Siuhi and Mussa, 2007). Studies differ as to whether variance in speeds contributes to crash rates.…”
Section: Mixed Trafficmentioning
confidence: 99%
“…Using simulation software Rakha et al (2005) concluded that providing separate lanes for trucks enhances performance as measured by speeds, fuel consumption and emissions. Not surprisingly, passenger vehicles benefit more from vehicle separation during peak hours when congestion is high (Siuhi and Mussa, 2007;Florida DOT, 2008) and on highway sections with extended upgrades. Lane restrictions are found to be more effective on highways with three or more lanes in each direction than on highways with only two (Stanley, 2009) and on freeways with limited access.…”
Section: Lane Restrictionsmentioning
confidence: 99%